Ontogenetic and Structural Variation of Mineralizations and Ossifications in the Integument within Ceratophryid Frogs (Anura, Ceratophryidae) - Quinzio, Silvia Inés (2012)
Ceratophryidae represent a monophyletic group of terrestrial and aquatic frogs inhabiting lowlands of South America where they are more diverse in semiarid environments of the Chaco region. Adult morphology of ceratophryids presents some features associated to terrestrial and fossorial life such as hyper-ossified skulls, spade feet for digging, among others. For anurans, different mineralized structures have been described in the integument as calcium reservoirs and related to the terrestrial life and water balance (e.g., the calcified layer and dermal ossifications). We describe the ontogeny of the integument in the three genera of ceratophryids (Chacophrys, Ceratophrys, and Lepidobatrachus) that inhabit in semiarid environments. Data obtained demonstrated the early acquisition of metamorphic transformations in the integument layers in larvae of Ceratophrys cranwelli and Lepidobatrachus spp. and a continuous increment in the thickness of them up to old postmetamorphic stages. The integument of ceratophryids develops calcium deposits as the calcified layer during postmetamorphic stages. Furthermore, dorsal shields are also present in adult stages independently of terrestrial versus aquatic lifestyles. While the calcified layer seems to be a feature of a fully developed integument, in which their layers have acquired the adult thickness, dorsal shields develop at premetamorphic stages in L. llanensis and postmetamorphic individuals of C. cranwelli. In ceratophryids, similar to other studied taxa (e.g., Brachycephalus spp.) dorsal shields develop via an intramembranous ossification in which the calcified layer does not precede its differentiation. Within anurans, the occurrence of dorsal shields in the monophyletic ceratophryids suggested a distinctive evolutionary history in the lineage. © 2012 Wiley Periodicals, Inc.